Estimating decay curves of neutralizing antibodies to SARS-CoV-2 infection. (27th June 2022) - Poehler, Elliot; Gibson, Liam; Lustig, Audrey; Moreland, Nicole J; McGregor, Reuben; James, Alex
Abstract: Estimating the longevity of an individual's immune response to the SARS-Cov-2 virus is vital for future planning, particularly of vaccine requirements. Neutralizing antibodies (Nabs) are increasingly being recognized as a correlate of protection and while there are many studies that follow the response of a cohort of people, each study alone is not enough to predict the long-term response. Studies use different assays to measure Nabs, making them hard to combine. We present a modelling method that can combine multiple datasets and can be updated as more detailed data becomes available. Combining data from seven published datasets we predict that the NAb decay has two phases, an initial fast but short-lived decay period followed by a longer term and slower decay period.